Vibrio cholerae O139 synonym bengal is closely related to Vibrio cholerae El Tor but has important differences. - Johnson, J A (1994)
Although Vibrio cholerae O139 synonym Bengal strains, from the current epidemics in India and Bangladesh, are closely related to seventh-pandemic strains, as shown by multilocus enzyme electrophoresis, Bengal strains are encapsulated and portions of the O1 antigen biosynthetic complex genes found in O1 strains are altered or lacking. Encapsulated Bengal strains showed resistance to killing by normal human serum. The presence of the capsule suggests the potential for bloodstream invasion in susceptible hosts and has profound implications for vaccine development.